The EAG Voltage-Dependent K+ Channel Subfamily: Similarities and Differences in Structural Organization and Gating - Barros, Francisco; de la Peña, Pilar; Domínguez, Pedro; Sierra, Luisa Maria; Pardo, Luis A. (Frontiers in Pharmacology, 2020)
EAG (ether-à-go-go or KCNH) are a subfamily of the voltage-gated potassium (Kv) channels. Like for all potassium channels, opening of EAG channels drives the membrane potential toward its equilibrium value for potassium, thus setting the resting potential and repolarizing action potentials. As voltage-dependent channels, they switch between open and closed conformations (gating) when changes in membrane potential are sensed by a voltage sensing domain (VSD) which is functionally coupled to a pore domain (PD) containing the permeation pathway, the potassium selectivity filter, and the channel gate. All Kv channels are tetrameric, with four VSDs formed by the S1–S4 transmembrane segments of each subunit, surrounding a central PD with the four S5–S6 sections arranged in a square-shaped structure. Structural information, mutagenesis, and functional experiments, indicated that in “classical/Shaker-type” Kv channels voltage-triggered VSD reorganizations are transmitted to PD gating via the α-helical S4–S5 sequence that links both modules. Importantly, these Shaker-type channels share a domain-swapped VSD/PD organization, with each VSD contacting the PD of the adjacent subunit. In this case, the S4–S5 linker, acting as a rigid mechanical lever (electromechanical lever coupling), would lead to channel gate opening at the cytoplasmic S6 helices bundle. However, new functional data with EAG channels split between the VSD and PD modules indicate that, in some Kv channels, alternative VSD/PD coupling mechanisms do exist. Noticeably, recent elucidation of the architecture of some EAG channels, and other relatives, showed that their VSDs are non-domain swapped. Despite similarities in primary sequence and predicted structural organization for all EAG channels, they show marked kinetic differences whose molecular basis is not completely understood. Thus, while a common general architecture may establish the gating system used by the EAG channels and the physicochemical coupling of voltage sensing to gating, subtle changes in that common structure, and/or allosteric influences of protein domains relatively distant from the central gating machinery, can crucially influence the gating process. We consider here the latest advances on these issues provided by the elucidation of eag1 and erg1 three-dimensional structures, and by both classical and more recent functional studies with different members of the EAG subfamily.